Avaliação dos efeitos dos níveis de ruído na saúde do trabalhador, resultantes da utilização de serra circular - Mahl, Luiza Gabriela dos Reis (2019)
The presence of noisy equipment in the workplace can cause damage to the auditory system of workers who are exposed to these sounds on a daily basis, generating symptoms and diseases characteristic of hearing loss. The circular saw is widely used in the construction field, specifically in carpentry, and it’s classified as an equipment that generates high levels of sound pressure. This paper aimed to analyze the working environment and health conditions of carpenters who use this equipment. The work was divided in two stages, being the first one a measurement, with the use of a decibelimeter, of the noise emitted by the saw during a working expediente (eight hours). The second stage consisted in the application of a questionnaire regarding the hearing health of 30 carpenters and the use of hearing protection by these workers. The results showed that ear protection may not be effective in cases of excessive exposure to these noises in the long-term.